MGPDI: modelo de gestión de la I+D+i en las organizaciones - Weber, Kival (2017)
A strategy to promote innovation in organizations consists of the adoption of Research, Development and Innovation (R+D+I) management systems. This paper aims at describing the current situation of the new R+D+I Management Model (MGPDI) that is applicable to any organization, independently of the size, type and activity. The novelty is in the definition of the: 1) Process Reference Model MR-MGPDI based on innovation best practices and on requirements of the Brazilian ABNT NBR 16501 and the Spanish AENOR UNE 166001-166002 standards; 2) Process Assessment Model MA-MGPDI based on the family of standards ISO/IEC 33000 for process assessment. Until December 2016 there are three goals: 1) to develop, test and publish two MGPDI guides (General Guide and Assessment Guide); 2) train the first implementation consultants, assessors and instructors; 3) perform three pilot of MGPDI implementation and assessment in organizations in southern Brazil, including tests with two online software support tools (SGPDI and MGPDI AA). MGPDI is a process model with great potential of replication in Latin America and Caribbean countries.